PSXIV-9 Narasin improves performance of grazing Nellore yearling bulls. (7th December 2018) - Polizel, D; Ferraz, M; Miszura, A; Barroso, J; Martins, A; Gonçalves, J; Limede, A; Cappellozza, B; Ferreira, E; Pires, A
Abstract: The objective of this trial was to determine the effect of narasin inclusion into a mineral salt on the performance of grazing bulls. Two hundred and forty Nellore yearling bulls were blocked by initial BW (193.1 ± 3.34 kg) and assigned to 32 paddocks (16 paddocks/treatment). Sixty-two paddocks of Brachiaria brizantha with 1 ha each were used, whereas each paddock was continuously grazed by 28 d, followed by a resting period of 28 d. Paddocks were rotated among treatments every 28 d to minimize the possible paddock variation. The experimental period lasted 112 d, divided into 4 periods of 28 d each. The treatments were: 1) negative control (no narasin; 0N ), and 2) 13 ppm of narasin/d (13N ; Zimprova ® ; Elanco, São Paulo, Brazil). Narasin was added on the mineral salt by adjusting its concentration in each 28-d period, according to the mineral intake (MI) during the previous one. The MI was evaluated on a weekly basis. Forage mass in the paddocks was measured by choosing two points upon entry and exit of the lot from each pasture. All data were analyzed using the PROC MIXED procedure of SAS. The ADG and MI were analyzed as repeated measures over time. There was no treatment × period interaction for ADG (P = 0.40) and MI (P = 0.27). Nonetheless, narasin inclusion into the mineral salt did not affect MI (0N = 64.1, 13N = 64.9 g/d; SEM = 1.77; P = 0.27), increased the ADG (0N = 0.555, 13N = 0.639 kg/d; SEM = 0.02; P < 0.01) and the final BW of the animals (N0 = 254.5, N13 = 263.6 kg; SEM = 4.62; P < 0.01). In summary, narasin inclusion into the mineral salt improved the performance of grazing yearling bulls.